A Novel Variant of Autosomal Recessive Lower Motor Neuron Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A genome-wide linkage analysis to map the underlying genetic defect was performed in a consanguineous African family with five patients affected with a novel variant of autosomal recessive lower motor neuron disease (LMND), in a study at Hopital Necker Enfants Malades and other centers, Paris, France.